Symptoms of Posttraumatic Stress Disorder in Middle School Students After the Covid-19 Outbreak - Rusmana, Nandang; Hafina, Anne; Ruyadi, Yadi; Nur, Lutfi (Jurnal Kajian Bimbingan dan Konseling, 2023)
COVID-19 bears various traumatic impacts on students. This study aims to identify PTSD symptoms in junior and senior high school students after the COVID-19 outbreak. The study was conducted using a cross-sectional survey method. Meanwhile, the data was collected using a problem checklist instrument. Further, the obtained data were analyzed using non-parametric statistics with the Mann-Whitney test to identify differences in PTSD symptoms based on gender and level of education. The results of the analysis show that symptoms appear in every physical, emotional, mental, behavioral, and spiritual aspect. Besides, we also found a significant difference in the level of anxiety disorder between male and female students after COVID-19, while there is no significantly distinct anxiety disorder between junior and senior high school students. In the end, we recommended that more in-depth research regarding the forms of intervention to reduce PTSD in students should be carried out.